2010
DOI: 10.18227/1982-8470ragro.v3i1.248
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento de plantas daninhas em área rotacionada com as culturas da soja, milho e arroz irrigado no cerrado de Roraima

Abstract: Levantamento de plantas daninhas em área rotacionada com as culturas da soja, milho e arroz irrigado no cerrado de Roraima). As famílias com maior ocorrência foram as Amaranthaceae, Euphorbiaceae e Poaceae. Dentre as espécies, 82,60% pertencem à classe botânica das dicotiledôneas. Palavras-chave -Composição Florística. Matocompetição. Plantas invasoras.Abstract -This study had as its objective to identify and to quantify the levels of population density of the weeds species in crops rotated with soybean, rice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 6 publications
0
16
0
18
Order By: Relevance
“…Other studies conducted in Roraima's cerrado have confirmed the species number predominance of the Fabaceae family (Cruz et al, 2009;Flores and Rodrigues, 2010;Albuquerque et al, 2013Albuquerque et al, , 2014.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Other studies conducted in Roraima's cerrado have confirmed the species number predominance of the Fabaceae family (Cruz et al, 2009;Flores and Rodrigues, 2010;Albuquerque et al, 2013Albuquerque et al, , 2014.…”
Section: Resultsmentioning
confidence: 57%
“…However, it is extremely important that 3 weed surveys are conducted over cultivations, in order to have greater representativeness of the invading species (Cruz et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These families were also representative in the soybeans rotated with maize and rice in Brazilian state Roraima (Cruz et al, 2009). These latter authors state that Asteraceae and Poaceae are the two main families of existing weeds in the cerrado, being present in different grain production systems, sugarcane, floodplain fields exploitation and pastures.…”
Section: Floristic Compositionmentioning
confidence: 99%
“…The highest population densities and the most harmful species in agricultural areas must be observed, from conducting floristic and phytosociological studies (Pitelli, 2000;Cruz et al, 2009).…”
Section: Introductionmentioning
confidence: 99%